Mindfulness at Work Increase Prosocial Behavior; Mediated by Job Satisfaction - Wiyata, Rahmat Alwi (Universitas Negeri Padang, 2025)
A change in work patterns that want to be more flexible due to technological developments makes people want to work independently. However, by working independently, they have challenges such as lack of job security and income uncertainty. So that these conditions require independent workers to always have good psychological well-being and social behavior in order to survive the pressure of work. Therefore, this study discusses the effect of mindfulness at work on prosocial behavior mediated by job satisfaction. In this study using 255 respondents who are independent workers who were then processed using the SmartPLS 4 application: 1) Mindfulness has a positive and significant effect on Prosocial Behavior, 2) Mindfulness has a positive and significant effect on Job Satisfaction, 3) Job Satisfaction has a positive and significant effect on Prosocial Behavior, and 4) Job Satisfaction mediates positively and significantly the effect of Mindfulness on Prosocial Behavior.